Especificidade do apetite ao sódio: uma possível contribuição hormonal - David, Richard Boarato (2006)
The hypothesis of a synergy between two hormones responsible for sodium conservation, aldosterone and angiotensin II (ANG II), explains the expression of a characteristic of sodium appetite, hypertonic NaCl intake, in a hypovolemic animal. Hypertonic NaCl intake can be induced in normovolemic rats that received a combined treatment of mineralocorticoid and ANG II at individual doses not sufficient to induce sodium intake (paradigmatic synergy test). Considering the motivation to specific sodium intake another characteristic of sodium appetite, the objective of the present dissertation was to find out a role for the interaction between mineralocorticoid and ANG II on the specificity of sodium appetite. Sprague-Dawley Holtzman rats (≅ 300 g b.w.) were housed with access to water and one or more palatable (0.01 M KCl, 0.05 mM CaCl2, 0.15 M NaHCO3, 0.15 M NaCl) or hypertonic (0.50 M NaCl) mineral solutions for ingestion. In two-bottle tests, a bottle contained water and another bottle contained either 0.01 M KCl, 0.15 M NaHCO3, 0.15 M NaCl or 0.50 M NaCl. In five-bottle tests, a bottle contained water and each one of the remaining four bottles contained either 0.01 M KCl, 0.05 mM CaCl2, 0.15 M NaHCO3 or 0.15 M NaCl, respectively. In sodium depletion tests, intact rats received each a 10 mg sc. injection of furosemide or vehicle followed by 24 h access to sodium deficient food and water. Then, food was removed and mineral solutions and water were offered for recording their intake (sodium appetite test). In the paradigmatic synergy test, the animals received daily single sc injection of 2.5 mg of deoxycorticosterone acetate (DOCA) or sunflower oil (vehicle) for three days and a left lateral cerebroventricular injection of 50 ng of ANG II four hours after the last DOCA or oil injection. Fluid intake record began immediately after ANG II injection and food removal. The daily intake record showed no preference for any solution or water when animals had access to five bottles. Sodium depletion induced a preferential sodium intake, with higher NaCl than NaHCO3 intake, in either two- or five-bottle sodium appetite tests. DOCA alone enhanced the daily 0.15 M NaCl and NaHCO3 intake, but did not alter KCl or 0.50 M NaCl intake in two-bottle tests. In the paradigmatic tests with normovolemic animals, ANG II combined to oil induced the ingestion of all three palatable mineral solutions (KCl, NaHCO3, NaCl) and water, in two-bottle tests, and preference for NaHCO3 in five-bottle tests. DOCA pretreatment enhanced only sodium solution intake, particularly NaCl intake, induced by ANG II in two-bottle tests (0.15 M NaCl: DOCA/ANG II = 24.5 ± 6.7 ml/120 min. vs. OIL/ANG II = 9.2 ± 1.8 ml/120 min.; 0.15 M NaHCO3: DOCA/ANG II = 17.0 ± 1.8 ml/120 min. vs. OIL/ANG II = 14.6 ± 2.1 ml/120 min.; 0.01 M KCl: DOCA/ANG II = 9.8 ± 1.9 ml/120 min. vs. 11.9 ± 1.2 ml/120 min.), and enhanced by 80 % the total sodium solution intake in the beginning of the five-bottle test. The combined effect of DOCA with ANG II on the induction of 0.50 M NaCl intake in a two-bottle test was replicated in our animals. The results from the paradigmatic synergy test are coherent with results from sodium appetite tests, suggesting that the mineralocorticoid may turn the effect of ANG II on mineral intake more selective to sodium intake. Thus, the combined ANG II and mineralocorticoid action could contribute to the expression of two characteristics of sodium appetite, not only the acceptance of hypertonic sodium solutions, but also the selective sodium intake.